KURIKULUM PENDIDIKAN AKHLAK KELUARGA DAN MASYARAKAT DALAM HADITS NABAWI - Fitroh Hayati; Laksmi Dewi (Edukasi Islami: Jurnal Pendidikan Islam, 2014)
Islamic Sharia is very attentive to all human needs, whether in relation to his personal benefit and social environment where he lives regardless of race, color, sex, or social status. Things that made the difference between a Muslim by another Muslim who is only one, namely piety. Moral education curriculum in the Prophetic hadith is comprehensive covering all aspects of moral education. The whole hadith about morals included in this study contains guidance on the practice of noble moral values that are needed by every Muslim in his life in this world, related to relationship with Allah Â -al-KhÄliq- and interaction with fellow beings. The formulation of moral education curriculum in the Prophetic hadiths very comprehensive increasingly punctuated with various moral guidance that should adorn every Muslim personally, which can be divided according to their interactions; (1) character to the parents; (2) character between husband and wife, both moral husband to wife and vice versa; (3) character to relatives; (4) morality to children; (5) characterto servant; (6) character to neighbors; (7) character to fellow Muslims; (8) character to non-Muslims; and (9) character to the animals.The entire hadith morals included in this study include the basics such noble character; guide at the same motivation to give the things that can bring benefits to the others, and prevent things that could bring harm to others; be gentle; put something in place; and fulfill the rights to other parties in accordance with their rights and avoid injustice by taking or impede the rights of others. The entire educational instruments contained in the moral education curriculum illustrates a perfection of moral education process, where it shows the perfection of Islam